2012
DOI: 10.1002/fuce.201200080
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of Interfaces between Lanthanum Contained Glass and Two Different Electrolytes for SOFC Applications

Abstract: The diffusion couples of lanthanum based strontium borosilicate glass with two different (high and low temperature) electrolytes have been heat‐treated at 850 and 800 °C, respectively, for 5, 100, and 750 h to understand the mechanism of interface formation and growth. These prepared diffusion couples have been characterized using various techniques like X‐ray diffraction (XRD), scanning electron microscope (SEM), X‐ray dot mapping, and electron probe microanalysis (EPMA). XRD revealed no detrimental phase for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…It has been reported in the literature that at high temperatures, grain boundaries can coalesce, leading to an increase in particle sizes and a decrease in their associated FWHM. 44,45 This series of XRD patterns agrees with this hypothesis, indicating a thermally driven interaction of the coating with the surfaces of the LNMO particles.…”
Section: Xrd Analyses Of the Cathode Particlessupporting
confidence: 76%
See 2 more Smart Citations
“…It has been reported in the literature that at high temperatures, grain boundaries can coalesce, leading to an increase in particle sizes and a decrease in their associated FWHM. 44,45 This series of XRD patterns agrees with this hypothesis, indicating a thermally driven interaction of the coating with the surfaces of the LNMO particles.…”
Section: Xrd Analyses Of the Cathode Particlessupporting
confidence: 76%
“…When θ new < θ initial at elevated temperatures, there is a corresponding increase in d and a change in the lattice parameters . The FWHM of the corresponding peaks can be described as normalF normalW normalH normalM = k λ / L .25em nobreak0em0.25em⁢ cos nobreak0em.25em⁡ θ where L is the particle size, and k is the crystallite shape factor (e.g., a good approximation is a value of 0.9). , The trends for FWHM did not exhibit a significant change with an increase in temperature for the HT-XRD analyses of the bare LNMO particles, which indicated that the particle size remained consistent up to 900 °C. Figure depicts the XRD plots for pristine, LZ25-coated, LZ50-coated, and LZ75-coated LNMO particles at RT.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ca 2+ , La 3+ and Sr 2+ have diffused considerably out of the glass composite matrix. Usually the zirconate phases form at the interface . In spite of diffusion of the strontium and calcium, no strontium/calcium zirconate could be seen at the joint region.…”
Section: Resultsmentioning
confidence: 99%
“…The molar ratio of silicon to total network former is represented by X Si assuming that no BO 4 are linked to each other [19]. One other term, which gives the probability of silicate coordinated to BO 4 is given as: …”
Section: Glass Network Connectivitymentioning
confidence: 99%